Informal seed traders: The backbone of seed business and African smallholder seed supply - Sperling, Louise; Gallagher, Patrick; McGuire, Shawn; March, Julie; Templer, Noel (MDPI, 2020)
To work well and be sustainable, seed systems have to o er a range of crops and varieties of good quality seed and these products have to reach farmers, no matter how remote or poor they may be. Formal seed sector interventions alone are not delivering the crop portfolio or achieving the social and geographic breadth needed, and the paper argues for focus on informal seed channels and particularly on traders who move ‘potential seed’ (informal or local seed) even to high stress areas. This paper provides the first in-depth analysis on potential seed trader types and actions, drawing on data collected on 287 traders working in 10 African countries. The research delves into four themes: the types and hierarchies of traders; the technical ways traders manage seed using 11 core practices; the price di erential of +50% of potential (local) seed over grain, and the pivotal roles which traders play in remote and crisis contexts. Traders are the backbone of smallholder seed security and need to be engaged, not ignored, in development and relief e orts. An action framework for leveraging seed trader skills is presented, with the paper addressing possible legal and donor constraints for engaging such market actors more fully.